Robust Proportional–Integral Sliding Mode Control for Induction Motors with Input Time Delay - Garcia, Saulo Crnkowise; Souza, Lucas Carvalho [UNESP]; Silva, Luciano de Souza da Costa e; Seixas, Falcondes José Mendes de [UNESP] (MDPI, 2023)
This paper proposes a control strategy applied to a three-phase induction motor (TIM) subject to parametric uncertainties, perturbations, and input time delay, whose primary objective is to achieve high-performance speed–torque control. The control design involves a predictive sliding mode observer (P-SMO) and a robust proportional–integral sliding mode control (PISM), aimed at reducing the detrimental effects of time delay and perturbations. The proposed control strategy’s effectiveness is investigated through computational simulations, carried out for different scenarios, whose distinctions focus on the consideration of delay in the feedback signals, the predictive character of the sliding mode observer, and the type of controller used. The presented results show the superior performance of the PISM controller compared with the classic PI controller for all tested scenarios. In the test scenario that considers the transport delay in the feedback signals, the sliding mode observer (SMO) without prediction does not stabilize the system, requiring the application of P-SMO to ensure stability and accurate tracking of the TIM speed reference.
Keywords: field oriented control; induction motor; input time delay; proportional–integral control; sliding mode control